(Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C high‐entropy ceramics with low thermal conductivity. Issue 10 (28th May 2018) - Yan, Xueliang; Constantin, Loic; Lu, Yongfeng; Silvain, Jean‐François; Nastasi, Michael; Cui, Bai
Abstract: A novel high‐entropy carbide ceramic, (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )C, with a single‐phase rock salt structure, was synthesized by spark plasma sintering. X‐ray diffraction confirmed the formation of a single‐phase rock salt structure at 26‐1140°C in Argon atmosphere, in which the 5 metal elements may share a cation position while the C element occupies the anion position. (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )C exhibits a much lower thermal diffusivity and conductivity than the binary carbides HfC, ZrC, TaC, and TiC, which may result from the significant phonon scattering at its distorted anion sublattice. (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )C inherits the high elastic modulus and hardness of the binary carbide ceramics.